Inovasi Media Pembelajaran Biologi: Validasi Poster Virus pada Materi Mikroorganisme Kelas X (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
Viruses are among the most challenging topics in biology learning because of their microscopic and abstract nature, which often leads to misconceptions among students. Therefore, innovative learning media are required to present viral concepts more clearly and attractively. This study aimed to develop and validate a poster entitled Structure of Viruses as a biology learning medium for tenth-grade students. The research employed a development method using the ADDIE model, but limited to the stages of analyze, design, develop, and evaluate. Validation instruments were assessed by two validators: one expert in virology content and one expert in biology learning media. The collected data were analyzed descriptively to determine the feasibility of the poster. Validation by the content expert resulted in an average score of 76.00, categorized as valid, indicating that the poster is feasible with moderate revisions, especially in terms of content completeness according to the curriculum. Validation by the media expert obtained an average score of 89.09, categorized as very valid, suggesting that the poster is feasible with minor revisions, particularly on the language aspect. It is concluded that the developed virus poster is suitable for use as biology learning media. Future research is recommended to extend poster development to virus replication topics, including lytic and lysogenic cycles, and to involve biology teachers as validators for practical assessment.
Keywords: poster, validity, virus, biology learning media